(untitled) (LACCEI, 2024)
In this study, an adaptation of the classical Horseshoe Vortex Method is performed to model the interaction of two or more lifting surfaces employing the generalized Kutta Joukowski theorem, which allows computing the lift produced by both inside and outside vortices. The resulting model was validated against wind tunnel tests for a canard airplane and showed good results for lift and induced drag predictions, especially before the region of flow detachment. The panel method obtained is useful for computing preliminary aerodynamic characteristics of an aircraft with a non-conventional wing configuration considering the respective model limitations and assumptions. Thus, a case study comparing the aerodynamic performance of the conventional and tandem wing layout configurations for a small fixed-wing UAV of 10 Kg of maximum take-off weight is developed. Among the most important results, it was found that the tandem-configuration aircraft showed a reduction of 12% of the lift generated compared with the lifting-line theory prediction when forward and rear wings aerodynamic interaction was considered. Also, for the tandem configuration aircraft, it was encountered to have a larger range of applicability due to its smaller size however, the conventional one showed less interference in the airflow between the wing and horizontal stabilizer, consequently, better aerodynamic efficiency.